ANALYSIS OF "JUANG TECH" ONLINE ORDERING APPLICATION USING QR CODE IN COFFEE SHOP IN BIREUEN REGENCY, ACEH - T. Irfan Fajri; Muazziss Najmi (Journal of Innovation Research and Knowledge, 2024)
The aim of this research is to analyze "Juang Tech" online ordering application using QR Code in Coffee Shop in Bireuen Regency, Aceh. The method used in this research uses descriptive qualitative methods. The research results show that Qriviti provides a more complete point of sale system that can be accessed via smartphone, tablet and personal computer. By using the available point of sale applications, cafe or restaurant owners can easily manage transaction processes, sales recording, stock management, and financial reports from any device chosen. The business tobusiness offering includes integration of a QR Code based ordering system and advanced point of sale solutions with existing operations in restaurants, cafes, and other eating places. Digital marketing strategies are key for Qriviti in expanding the reach and strengthening brand awareness. Through the use of social media, search engine optimization, relevant content, segmented email campaigns, and collaboration with influencers